Survey of students' Interest in Martial Arts at Sumber Mulya Elementary School Pelepat Ilir District Bungo Regency - Sugeng Purwanto; Dody Tri Iwandana; Baskoro Pandu Aji (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
This study aims to determine how much students' interest in martial arts is in high school students at 183/II Sumber Mulya Elementary School, Pelepat Ilir District, Bungo Regency. This type of research is included in quantitative descriptive research. The population in this study were students in grades VI, V, and VI at the 183/II Sumber Mulya Elementary School, Pelepat Ilir District, Bungo Regency, with a total of 28 students. The sampling technique used was Total Sampling. The research instrument used a questionnaire. The validity test of the rxy calculation are compared with the r table with a significant level of 5%. If rxy > rtable then the instrument is declared valid. The reliability test showed a score of 0, 734 if the alpha value> 0.6 then the instrument was reliable. Data analysis in this study used descriptive statistical analysis with SPSS software version 25. The results showed that the interest of grade VI, V, and VI students at SD 183/II Sumber Mulya, Pelepat Ilir District, Bungo Regency towards martial arts was high with an interest percentage of 71 ,42% with 20 students. Students who have low interest are 28,58% with 8 students. Based on these data it can be said that students' interest in martial arts is in high school students at 183/II Sumber Mulya Elementary School, Pelepat Ilir District. Bungo including high. It is hoped that this research can be used as an opening to decide which sports will be held as extracurricular activities at the 183/II Sumber Mulya Elementary School, Pelepat Ilir District, Bungo Regency. Keywords: Interests, Sports, Martial Arts